2003
DOI: 10.1023/b:clin.0000006819.21361.03
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 regulates membrane induced activation of matrix metalloproteinase-2 in osteosarcoma cells

Abstract: To study the role of the metastasis associated protein S100A4, an osteosarcoma cell line (OHS) with a high level of this protein was transfected with a vector containing a ribozyme that degrades S100A4 mRNA and, as controls, OHS cells were transfected with the vector alone. We have followed up our previous investigation (Bjørnland et al. 1999) by a detailed investigation of these cell lines' synthesis of MMP and TIMP proteins at different cell densities. It is shown that the cell lines with a low S100A4 level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 53 publications
1
43
1
Order By: Relevance
“…Down-regulation of S100A4 with ribozyme reduced the activity of several MMPs, including MMP2, as well as cell motility and invasiveness (55,56). On the other hand, treatment of tumor or endothelial cells with S100A4 increased their proteolytic activity, in particular, the activity of MMP13, and invasive growth (24,27).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of S100A4 with ribozyme reduced the activity of several MMPs, including MMP2, as well as cell motility and invasiveness (55,56). On the other hand, treatment of tumor or endothelial cells with S100A4 increased their proteolytic activity, in particular, the activity of MMP13, and invasive growth (24,27).…”
Section: Discussionmentioning
confidence: 99%
“…(35) Noviskaya et al reported that S100A4 stimulation was involved in the activation of both phospholipase C and protein kinase C. (16) A possible relationship between S100A4, matrix metalloproteinases, and invasive capacity has also been reported. (36,37) Extracellular function of S100A4 might also include angiogenesis. (17,38) Thus, further research is needed to clarify the intercellular and extracellular mechanisms of S100A4 involvement in the progression of ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The S100A4 gene is reported to confer invasive characteristics to various cancer cells; however, its role in the invasion and metastasis of CaP is yet unknown (11). Next, we analyzed the effect of S100A4 gene suppression on the invasive capability of highly invasive and metastatic CaP cells PC-3 by employing an in vitro chemoinvasion assay.…”
Section: Effect Of S100a4 Gene Knockdown On Invasive Capability Of Pcmentioning
confidence: 99%